Teaching before and during COVID-19: A survey. Issue 2 (3rd April 2023) - Allgood, Sam; McGoldrick, KimMarie
Abstract: Past survey evidence shows little change in how economists teach, but the pandemic forced change upon faculty. This survey investigates what that change looked like, whether faculty feel that the changes were for the better or worse for themselves and their students, and what changes faculty will continue post-pandemic.